Generation of American mink induced pluripotent stem cells: a protocol - I. E. Pristyazhnyuk; A. G. Menzorov (Вавиловский журнал генетики и селекции)
Mammalian genome reprogramming has been studied for more than half a century. First, Sir John Gurdon showed the possibility of diﬀerentiated cell genome reprogramming by enucleated oocyte factors in 1962. Dr. Shinya Yamanaka produced induced pluripotent stem (iPS) cells from mouse ﬁbroblasts by the use of just four transcription factors in 2006: Oct4, Klf4, Sox2, and c-Myc. Generation of iPS cells put a question about the reprogramming completeness: do genes derived from ﬁbroblasts retain their expression? And are the features of iPS cells in compliance with those of embryonic stem (ES) cells that serve as a standard? To date, iPS cells have been produced for tens of species, while ES cells, for less than twenty. In 1993 American mink (Neovison vison) ES cells were produced in the Institute of Cytology and Genetics SB RAS. That created a unique opportunity for comparison of induced and embryo-derived pluripotent cells. In 2015 we produced American mink iPS cells and showed ﬁbro-blast genome reprogramming at the level of gene expression and divided genes into four groups: reprogrammed, with intermediate expression, non-reprogrammed, and the ones with a “novel” expression pattern. Thus, an opportunity to study pluripotency and diﬀerentiation on two pluripotent cell types, ES and iPS cells, was added for one more species. In this article we present a detailed protocol for generation of American mink iPS cells with human OCT4, KLF4, SOX2, and cMYC genes. In addition, we brieﬂy describe necessary methods for their analysis: morphology, cytogenetic analysis, PCR with reverse transcription for the presence of pluripotency “marker” genes, and teratoma formation test in immunodeﬁcient mice. This protocol allows reliable and efficient generation of American mink iPS cells from embryonic ﬁbroblasts.